Fruit Rot of Durian Caused by Phytophthora palmivora - Lim, T.K; Chan, L.G (1986)
A severe fruit rot of durzan fruits in Bentong and Raub in Pahang; Dengkil in Selangor; Muar and Kluang in Johore was found to be caused by a Phytophthora sp. Besides fruits, isolates of the pathogen were also capable of infecting roots, stem and leaves of durian. The isolates were identified as Phytophthora palmivora, cross-inducing (heterothallic) and of the A 1 mating type, producing spores when paired with a standard A2 mating type of P. palmivora and another A2 isolate from cocoa but not with an A 1 mating type of P.parasitica.